Effects of Brief Daily Periods of Unrestricted Vision during Early Monocular Form Deprivation on Development of Visual Area 2 - Zhang, Bin (Association for Research in Vision and Ophthalmology, Inc., 2011)
PURPOSE. Providing brief daily periods of unrestricted vision during early monocular form deprivation reduces the depth of amblyopia. To gain insights into the neural basis of the beneficial effects of this treatment, the binocular and monocular response properties of neurons were quantitatively analyzed in visual area 2 (V2) of form-deprived macaque monkeys. METHODS. Beginning at 3 weeks of age, infant monkeys were deprived of clear vision in one eye for 12 hours every day until 21 weeks of age. They received daily periods of unrestricted vision for 0, 1, 2, or 4 hours during the form-deprivation period. After behavioral testing to measure the depth of the resulting amblyopia, microelectrode-recording experiments were conducted in V2. RESULTS. The ocular dominance imbalance away from the affected eye was reduced in the experimental monkeys and was generally proportional to the reduction in the depth of amblyopia in individual monkeys. There were no interocular differences in the spatial properties of V2 neurons in any subject group. However, the binocular disparity sensitivity of V2 neurons was significantly higher and binocular suppression was lower in monkeys that had unrestricted vision. CONCLUSIONS. The decrease in ocular dominance imbalance in V2 was the neuronal change most closely associated with the observed reduction in the depth of amblyopia. The results suggest that the degree to which extrastriate neurons can maintain functional connections with the deprived eye (i.e., reducing undersampling for the affected eye) is the most significant factor associated with the beneficial effects of brief periods of unrestricted vision.